2014
DOI: 10.1002/smll.201400358
|View full text |Cite
|
Sign up to set email alerts
|

Sonication‐Induced Formation of Size‐Controlled Self‐Assemblies of Amphiphilic Janus‐Type Polymers as Optical Tumor‐Imaging Agents

Abstract: In this study, amphiphilic Janus-type polymers were synthesized via ring-opening metathesis polymerization (ROMP), multiple vicinal diol formation, and grafting of poly(ethylene glycol) monomethyl ether (mPEG). These amphiphilic polymers formed self-assemblies, which were a mixture of micelles and multimicellar aggregates, in water. By choosing suitable Janus-type polymers and irradiating an aqueous solution of polymers using a sonicator, either small micelles or large multimicellar aggregates were obtained se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…23−27 Most recently, we reported that Janus-type amphiphilic polysaccharide analogues conjugated with ICG dye moieties could be used for the ultrarapid visualization of tumor tissues by optical imaging in vivo (Figure 1a). 28 During the course of our study, we found that by replacing the hydrophobic alkyl chains in Janus-type amphiphilic polymers with hydrophobic ICG dye derivatives, self-assemblies with an ICG dye-condensed hydrophobic core were formed (Figure 1b). With a view to clinical application, the naturally occurring polysaccharide hyaluronic acid (HA) was chosen as the main chain polymer of the amphiphilic Janustype polymers.…”
Section: ■ Introductionmentioning
confidence: 96%
“…23−27 Most recently, we reported that Janus-type amphiphilic polysaccharide analogues conjugated with ICG dye moieties could be used for the ultrarapid visualization of tumor tissues by optical imaging in vivo (Figure 1a). 28 During the course of our study, we found that by replacing the hydrophobic alkyl chains in Janus-type amphiphilic polymers with hydrophobic ICG dye derivatives, self-assemblies with an ICG dye-condensed hydrophobic core were formed (Figure 1b). With a view to clinical application, the naturally occurring polysaccharide hyaluronic acid (HA) was chosen as the main chain polymer of the amphiphilic Janustype polymers.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Among the physicochemical parameters of NPs, particle size is a critical characteristic to determine the NP biodistribution and accumulation in the tumour tissue in vivo, thus providing a further important consideration for improved clinical effects. [13][14][15][16] The large NPs are rapidly taken up by the liver and spleen, resulting in a reduced accumulation in the tumors. The small NPs show reduced phagocytic capture of the NPs by the cellular immune system, leading to a longer circulation time and the subsequent accumulation in tumor tissues attributed to the enhanced permeability and retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%
“…74) [318]; (7) a tris(norbornenecarboxylate) connected to a carbon nanotube [319]; (8) bis(norbornenecarboxylate ester)s (e.g. 73) [320]; (9) 5-ethylidenenorbornene (68) [321], including its use as a part of a self-healing system [322]; (10) vinylnorbornene [323]; (11) tetracyclododecene (69) [324]; (12) norbornadienes connected to various hydrophobic groups, including a steroid system [325]; (13) dicyclopentadiene [326,327,328,329,330,331,332,333,334,335,336], including polymerizations performed in the presence zinc oxide nanoparticles [337], urea formaldehyde microcapsules [338],mildly oxidized graphene oxide [339], barium titanate [340], and high internal phase emulsions [341,342]; (14) the norbornadiene-anthracene Diels-Alder adduct (76) [343,344]; (15) norbornenedicarboxylate esters connected to cyanobiphenyl groups [345], to anthracene groups [346], and to nitroxide groups (e.g. 79) [347]; (16) the three stereoisomeric dimethyl norbornenedicarboxylates (determination of the relative rates of ROMP) [348]; …”
Section: Polymerization Reactionsmentioning
confidence: 99%